Event Management Praktik Lapang Mahasiswa Universitas Koperasi Indonesia di Daerah Istimewa Yogyakarta - Ami Purnamawati (LPPM Universitas Koperasi Indonesia, 2023)
Learning process for seventh semester students of Ikopin University is conducted both classical and field classes. One of the field activity classes named Praktik Lapang (Cooperative Field Practice) is organized by the university committee consisted of the all rank academic officials. Praktik Lapang as a formal education activity is managed by considering the aspects of event management. All activities are based on the Term of Reference (ToR) designed by the committee consisting of activity background, aims and objectives, theme, budget, venues, personnels, as well as the steps of activities. In 2023 there were 369 participants – divided into 65 groups - had the opportunity to get involved in 65 cooperatives of Daerah Istimewa Yogyakarta Province. They conducted various activities for one month as designed by board of cooperative as well as by the university, such as participating in cooperative activities both business and administration stuffs, then writing the report of the activity. As the students who study cooperative they also must become cooperative extension agents to the society and also promote Ikopin University to some high schools there. While conducting the programs, the counselor monitored each group on the site and there was also a counselor for guiding report writing. During the main activities the students could learn more about small business, culture and tourism in Yogyakarta